2022
DOI: 10.1055/s-0041-1740203
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Perioperative Anesthetic Concerns in Simple and Complex Craniosynostosis Cases: A Retrospective Study

Abstract: Background We compared intraoperative and postoperative anesthetic parameters between simple (S-single suture) and complex (C-more than one suture) craniosynostosis cases. Materials and Methods Data was collected from a retrospective review of anesthetic and postoperative records of patients who underwent craniosynostosis correction surgery between April 2014 and August 2019. Pearson’s chi-square and independent sample t-tests were used for analysis. Results We analyzed data of 98 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…They also reported post-operative complications of hypotension, hypothermia, metabolic acidosis, blood loss, fever of unknown origin, and hyperglycemia [20]. The evaluation of incidents in the reported cohort showed clinically significant metabolic or hemodynamic events, despite the wide range of problems described in the literature [11,12,14,17,19,21,22]. These findings imply that those children require close monitoring for at least 24 hours following surgery.…”
Section: Highmentioning
confidence: 89%
See 2 more Smart Citations
“…They also reported post-operative complications of hypotension, hypothermia, metabolic acidosis, blood loss, fever of unknown origin, and hyperglycemia [20]. The evaluation of incidents in the reported cohort showed clinically significant metabolic or hemodynamic events, despite the wide range of problems described in the literature [11,12,14,17,19,21,22]. These findings imply that those children require close monitoring for at least 24 hours following surgery.…”
Section: Highmentioning
confidence: 89%
“…A total of 11 studies were included in this review, with 21456 patients diagnosed with craniosynostosis, and more than half of them were males. Eight studies were conducted in the United States (USA) [10][11][12][13][14][15][16][17], one in Brazil [18], one in India [19], and one in Turkey [20]. We found that the nonsyndromic craniosynostosis weighed much more than the syndromic incidence.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 92%
See 1 more Smart Citation
“…Ayrıca traneksamik asit plazmini inhibe eder. Traneksamik asitin 10 mg kg -1 bolus dozlarından sonra ameliyat süresince 5 mg kg -1 sa -1 infüzyon uygulamalarının pediatrik kraniyofasiyal ameliyatlarda kanamayı ve kan transfüzyonunu azalttığı, sistemik hemostazı etkilemeden D-dimer seviyesinde artışı önlediği gösterilmiştir (23,25). Traneksamik asit uygulamasının kan kaybını ve kan transfüzyonu sıklığını azalttığı, Zapata-Copete ve ark.…”
Section: Monitörizasyonunclassified
“…Hipervolemik hemodilüsyon, kan alınmadan viskozitenin sıvı yükleyerek azaltılması tekniğidir. Genellikle kolloid sıvı preoperatif dönemde 15 mL kg -1 yüklenir (14,23). Ameliyat sırasında gelişebilecek hipotermi koagülopatiye yol açacağından normoterminin sağlanması önemlidir (7,11).…”
Section: Kan Kaybını Azaltma Yöntemleriunclassified